Heart rate variability changes at 2400 m altitude predicts acute mountain sickness on further ascent at 3000–4300 m altitudes - Karinen, Heikki M.; Uusitalo, Arja; Vähä-Ypyä, Henri; Kähönen, Mika; Peltonen, Juha E.; Stein, Phyllis K.; Viik, Jari; Tikkanen, Heikki O. (Frontiers in Physiology, 2012)
Objective If the body fails to acclimatize at high altitude, acute mountain sickness (AMS) may result. For the early detection of AMS, changes in cardiac autonomic function measured by heart rate variability (HRV) may be more sensitive than clinical symptoms alone. The purpose of this study was to ascertain if the changes in HRV during ascent are related to AMS. Methods We followed Lake Louise Score (LLS), arterial oxygen saturation at rest (R-SpO2) and exercise (Ex-SpO2) and HRV parameters daily in 36 different healthy climbers ascending from 2400 m to 6300 m altitudes during five different expeditions. Results After an ascent to 2400 m, standard deviation (RMSSD2 min), high-frequency power (HF2 min) of HRV were 17-51 % and Ex-SpO2 was 3% lower in those climbers who suffered from AMS at 3000- 4300 m than in those only developing AMS later (≥ 5000 m) or not at all (all p < 0.01). At the altitude of 2400 m RMSSD2 min ≤ 30 ms and Ex-SpO2 ≤ 91% both had 92% sensitivity for AMS if ascent continued without extra acclimatization days. Conclusions Changes in supine HRV parameters at 2400 m were related to AMS at 3000-4300 m Thus, diverse analyses of HRV could offer potential markers for identifying the climbers at risk for AMS.